Conserving a geographically isolated Charaxes butterfly in response to habitat fragmentation and invasive alien plants - Casparus J. Crous; James S. Pryke; Michael J. Samways (Koedoe: African Protected Area Conservation and Science, 2015)
In South Africa, much of the forest biome is vulnerable to human-induced disturbance. The forest-dwelling butterfly Charaxes xiphares occidentalis is naturally confined to a small forest region in the south-western Cape, South Africa. Most of the remaining habitat of this species is within a fragmented agricultural matrix. Furthermore, this geographical area is also heavily invaded by alien plants, especially Acacia mearnsii. We investigated how C. x. occidentalis behaviourally responds to different habitat conditions in the landscape. We were particularly interested in touring, patrolling and settling behaviour as a conservation proxy for preference of a certain habitat configuration in this agricultural matrix. Remnant forest patches in the agricultural matrix showed fewer behavioural incidents than in a reference protected area. Moreover, dense stands of A. mearnsii negatively influenced the incidence and settling pattern of this butterfly across the landscape, with fewer tree settlings associated with more heavily invaded forest patches. This settling pattern was predominantly seen in female butterflies. We also identified specific trees that were settled upon for longer periods by C. x. occidentalis. Distance to a neighbouring patch and patch size influenced behavioural incidences, suggesting that further patch degradation and isolation could be detrimental to this butterfly. Conservation implications: We highlight the importance of clearing invasive tree species from vulnerable forest ecosystems and identify key tree species to consider in habitat conservation and rehabilitation programmes for this butterfly. We also suggest retaining as much intact natural forest as possible. This information should be integrated in local biodiversity management plans.